The Last Slave Traders - Meunier, Pierre (Spectrum Books Ltd, 1999)
The Last Slave Traders dramatizes the mental and emotional subjugation, destruction of self-worth and the dehumanization and reduction to nothingness of employees by their whit employers.
Keywords: Africa(English); Drama